KEBIASAAN MAKANAN IKAN DI SITU GONGGONG, KABUPATEN PANDEGLANG, BANTEN - Neng Muliah; Forcep Rio Indaryanto; Ani Rahmawati; Muta Ali Khalifa; Desy Aryani; Erik Munandar (Jurnal Perikanan dan Kelautan, 2020)
Gonggong Lake is one of the lentic waters, located at Cipicung village Cikedal District Pandeglang Banten. Gonggong Lake is used as a source of water for irrigation rice fields, O. tilapia culture, tofu production, oncom, social activity, and fishing. This causes made the availability of natural food and resulted in the change balance of ecosystems in the waters. Natural fish foods are the main factor needed in the process of growth, reproduction, and survival of fish. Fish food habits in nature are important to be studied as an effort to manage fishery resources. The study aimed to determine to identify fish food habits in Gonggong Lake. The study was conducted from July to August 2017 at 4 stations, i.e. 1) inlet I; 2) inlet II; 3) center of the lake, and 4) outlet. Fish and food habits identification was conducted at the laboratory of aquaculture, University of Sultan Ageng Tirtayasa. The results of this study in Gonggong Lake, there are 5 species of fish caught namely Oreochromis niloticus, Barbonymus gonionotus, Trichogaster trichopterus, Channa striata, and Glossogobius giuris. Food habits in Gonggong Lake  are dominated by herbivorous fish with main food of phytoplankton and plant parts. Natural foods are dominated by phytoplankton consist of the Chlorophyta, Chrysophyta, Cyanophyta, Cryptophyta, and Euglenophyta groups.